Development of a sandwich enzyme-linked immunosorbent assay for dTMP-GH fusion protein by rational immunogen selection - Wang, Song (AMB Express, 2017)
dTMP-GH is a chimeric protein containing a tandem dimer of thrombopoietin mimetic peptide (dTMP) fused to human growth hormone (hGH) prepared previously by our team. It shows significant bioactivity in promoting thrombocytopoiesis, but detection of intact dTMP-GH in plasma is still a challenge due to the presence of endogenous hGH. In this study, a rabbit polyclonal antibody with high affinity to dTMP was obtained with a BSA-conjugated immunogen composed of 20 amino acids sequence spanning two TMP and the linker. A monoclonal antibody termed as 3B2 was screened out by using immunizing mice with whole dTMP-GH, which was proved to simultaneously interact with rhGH, TMP-GH, and dTMP-GH, respectively. In this study, we developed a specific and sensitive sandwich enzyme-linked immunosorbent assay (ELISA) with two antibodies (one polyclonal and one HRP-conjugated monoclonal) to quantify dTMP-GH. The polyclonal antibody and HRP-conjugated monoclonal antibody 3B2 were applied as the capture antibody and detection antibody, respectively. A good correlation between ELISA and bicinchoninic acid (BCA) assay in the quantification of diluted dTMP-GH was observed (r(2) = 0.996). Meanwhile, the standard curve of this ELISA method was found in a linear relationship between 0.2 and 10 ng/mL in the presence of rabbit plasma. In vivo experiments demonstrate that the newly developed method is effective to detect dTMP-GH in rabbits, which paves the way for further pharmacokinetic evaluation.